SME Financing: Diversity of Sources and Specific Constraints in Morocco - DIDI SEDDIK, Mohamed Mouad; EL ADRAOUI, Fatima Ezzahra; RABAH–RABBOU, Mounir; JABBOURI, Jihad (Revue Internationale des Sciences de Gestion, 2024)
This article explores the financing constraints of small and medium-sized enterprises (SMEs) in Morocco, highlighting the specific challenges they face in accessing financial resources. First, we provide an overview of the financing options available in general, both internal and external, analyzing their characteristics, advantages and limitations. We then turn our attention to the context of Moroccan SMEs, which, although essential to economic growth and employment, face numerous financial constraints. These companies face obstacles that limit their access to bank credit, notably due to high collateral requirements. The aim of this study is to provide an in-depth analysis of the difficulties in accessing financing, while proposing avenues for financial support better adapted to the needs of Moroccan SMEs, in order to strengthen their potential for growth and sustainability.